Exploring the potential and constraints of smallholder aquaculture in marginalized saline areas in Pakistan - Rossignoli, Cristiano; Obi, Chinedu; Ali, Syed (WorldFish, 2022)
Pakistan is the sixth-most populous country in the world, with a population of approximately 225 million. More than 20% of the population lives below the national poverty level (World Bank, 2021). •Fishery and aquaculture have the potential to significantly reduce poverty and food insecurity in Pakistan (Rehman et al., 2019).•Pakistan ranks low in global aquaculture production (FAO, 2022) -aquaculture produced 162,462 tons of fish in 2020. Over the past five years, the aquaculture sector has grown at a rate of approximately 1.5%.•Because of the arid and semi-arid climate, rainfall is scarce and irregular in most of the areas and contributes to salinity and waterlogging -salinity in the soil makes land unsuitable for growing crops: an opportunity for practicing “inland saline aquaculture” on lands not suitable for crop cultivation -11.1 million acres (4,49 million ha). •Despite the huge potential of saline aquaculture, the characteristics of the production systems in Pakistan are still unknown due to data deficiency, making it difficult to understand investment needs that will help in the sector's development.